Soil N and P affected reflectance signatures of individual Colophospermum mopane leaves - Ferwerda, J.G.; Skidmore, A. K.; Van Wieren, S.E.; Prins, H. H. T. (Journal of spatial science, 2006)
Reflectance and derivative spectra of greenhouse-grown mopane (Colophospermum mopane) were analyzed to investigate whether the interactive effect of soil phosphorus and nitrogen treatments on plant-chemical composition can be detected using non-destructive techniques. Reflectance spectra were affected by changes in soil nitrogen. Derivative spectra showed significant differences as a result of nitrogen and phosphorus treatment. Several spectral bands that showed different spectral signatures between soil treatments also showed significant correlation to condensed tannin, phosphorus and nitrogen concentration in mopane leaves. This shows the potential to detect the effect of soil properties on the plant's physiology with hyperspectral remote sensing.